The "service excellence chain": an empirical investigation in the healthcare field. Issue 6 (23rd March 2020) - Guglielmetti Mugion, Roberta; Musella, Flaminia; Di Pietro, Laura; Toni, Martina
Abstract : Purpose: The linkage between internal and external satisfaction is an understudied topic in the service field. This study aims to address this gap by proposing an original research model, the service excellence chain (SEC), that connects the internal and external perspectives by conjoining performance-excellence models and the service-profit-chain approach. Theoretical assumptions and quantitative measures are proposed by using advanced statistical techniques. Design/methodology/approach: The SEC is investigated through an empirical study in the healthcare sector, focusing on an Italian hospital and involving two of its core units. Qualitative and quantitative approaches were used. First, internal and external customer satisfaction were separately tested through structural equation modeling. The linkage between internal and external satisfaction is then proposed by mathematically defining a synthetic index, the internal and external customer satisfaction index (IEGSI), modeled through Bayesian networks (BNs) and object-oriented BNs to provide an overall measure able to predict organizational improvement. Findings: The distinct measured models show good internal validity and adequate fit both for patients' and employees' perspectives. The IEGSI allows rigorously connecting internal and external satisfaction by developing conjoint scenarios for organizational improvement. Originality/value: This study proposes the SEC model as an innovative way to connect internal and external satisfaction. The findings can be useful both for private and public organizations and may provide several useful insights for healthcare managers as well as for policy-makers in relation to developing strategies for improving service quality.